Challenges in global key account management in Finnish multinational organizations - Salminen, Hannu (My University, 2020)
Globalization has brought pressure for multinational companies to be competitive in pricing, quality and delivery, not only against local competition but also against global ones. As the world is globalizing and multinational organizations attain international customers the need for global key account management has increased. Finland and Finnish companies are more reliant on international business than perhaps ever before. The purpose of this study is to analyze and define what are the challenges in global key account management in the studied Finnish multinational organizations. This questioned is answered by conducting a qualitative research, studying the internal and external challenges that face global key account management in academic and professional literature and in the studied Finnish multinational organizations. Global key account management is a business strategy and an organizational entity in which global organizations systematically select, evaluate and manage strategically important or potential global customers. Global key account management is a mixture of key account management and global account management, formed to answer to the needs of multinational companies wanting to centralize their global supplier processes. In the research five internal and four external challenges were discovered that affect global key account management in the studied Finnish multinational organizations. The most impactful internal challenge discovered from the interviews is the challenge of key account selection and the most impactful external challenge discovered from the interviews is the challenge of customer expectations. Based on the findings from the global key account management literature and from the studied Finnish multinational organizations managerial recommendations are given to prevent these challenges.

Globalisaatio on tuonut painetta monikansallisille yrityksille pysyä kilpailullisena hinnoittelussa, laadussa sekä toimituksessa. Kilpailua ei käydä ainoastaan paikallisia yrityksiä vastaan vaan globaalilla tasolla kaikkien kanssa. Globalisaatio on tuonut mukanaan kilpailun lisäksi myös kansainvälisiä asiakkaita, jonka vuoksi kansainvälisen avainasiakashallinnan tarve on lisääntynyt. Suomi ja suomalaiset yritykset ovat riippuvaisempia ulkomaisesta viennistä kuin ehkä koskaan ennen. Tämä on tuonut mukanaan niin kansainvälisen kilpailun kuin kansainväliset asiakkaatkin. Tämä tutkimuksen tarkoituksena on analysoida sekä määritellä kansainvälisen avainasiakashallinnan haasteet tutkimuksessa mukana olleille suomalaisille monikansallisille yrityksille. Tätä varten on muodostettu kvalitatiivinen tutkimus, jonka avulla määritellään kansainvälisen avainasiakashallinnan sisäiset ja ulkoiset haasteet tutkimuksessa mukana olleille yrityksille. Näitä haasteita pyritään löytämään akateemisesta kirjallisuudesta ja yritysten kanssa tehdyistä haastatteluista. Kansainvälinen avainasiakashallinta on yritysstrategia sekä organisatorinen itsenäinen kokonaisuus, jonka avulla systemaattisesti valitaan, arvioidaan sekä hallitaan kansainvälisiä avainasiakkaita. Kansainvälinen avainasiakashallinta on yhdistelmä kansainvälistä asiakashallintaa sekä avainasiakashallintaa. Tämän avulla pyritään paremmin vastaamaan kansainvälisten asiakkaiden tarpeisiin. Tutkimuksessa identifioitiin viisi sisäistä haastetta ja neljä ulkoista haastetta, jotka vaikuttavat kansainväliseen avainasiakashallintaan. Sisäisistä haasteista voimakkaimmin nousi esille avainasiakkaiden valintaprosessi -haaste ja ulkoisista haasteista esille nousi asiakasodotusten-haaste. Tutkimuksessa annetaan suosituksia näiden haasteiden ehkäisemiseen. Suositukset pohjautuvat akateemiseen kirjallisuuteen sekä haastatteluihin tutkittujen yritysten kanssa.
Keywords: Global key account management, internal challenges, external challenges, Finnish multinational organizations Kansainvälinen avainasiakashallinta, sisäiset haasteet, ulkoiset haasteet, suomalaiset monikansalliset yritykset